Regulatory responses to foodborne illness outbreaks in the United States and their implications for food safety - Prabhukhot, Grishma (Frontiers in Nutrition, 2026)
Foodborne outbreak investigations in the United States are inherently complex. Amid the evolving landscape of policy changes, scientific breakthroughs in disease detection, technological innovations, and globalized trade, there is an urgent need to build a resilient food safety system. This perspective article highlights the role of various regulatory bodies in two of the recent foodborne outbreaks, critically evaluating both the strengths and shortcomings in how these outbreaks were managed. Additionally, the FDA's New Era of Smarter Food Safety is discussed in brief to showcase how technologies such as Artificial Intelligence, blockchain, and Internet of Things (IoT) are advancing traceability, outbreak response, and prevention. This article argues that international policy alignment, targeted investment, and inclusive infrastructure development are essential for translating technological advancements into resilient and globally accessible food safety practices.